Evaluation of thermal comfort levels concerning the spatial arrangement in an operating room - Nelson Rodrigues (2015)
A person's thermal sensation is influenced by his physical activity and clothing, as well as by environmental parameters, such as air temperature, mean radiant temperature, relative air velocity and relative humidity of the air. The aim of this study regards the evaluation of thermal comfort levels experienced by the surgical staff at operating rooms. The methodology in this study was based on a survey on thermal sensation of the surgical staff using questionnaires. The assessment of the subjective thermal sensation in the operating room was provided by a total of 71 questionnaires. The results show an over-estimation of thermal sensation using the PMV (Predicted Mean Vote) calculation, as well as differences between regions on the studied operating room.